Studi Literatur : Analisis Pembelajaran Daring Anak Berkebutuhan Khusus di Masa Pandemi - Amelia Rizky Idhartono (Jurnal Studi Guru dan Pembelajaran, 2020)
The pandemic requires schools to conduct online learning. This is in accordance with the Circular Letter from the Ministry of Education and Culture which requires schools to hold online learning. This condition is a lot of obstacles, especially in teaching materials to children with special needs. obstacles faced by teachers and students include the problem of limited devices and quotas. In addition, it is necessary to creativity teachers in developing strategies that motivate children with special needs for interests and enjoy learning. This research is a literature study that examines research relevant to the topic of discussion. From the results of the discussion, teachers can use a variety of strategies, namely ASIK strategy and 5M strategy.